Endovascular treatment of a giant aneurysm of the proper hepatic artery: A case report - Thomas J. Vogl; Carolyn Enam Pi-Bansa; Kyriakos Oikonomou; John Bielfeldt; Hamzah Adwan (Radiology Case Reports)
Hepatic artery aneurysms (HAAs) are rare vascular abnormalities, accounting for 20% of all visceral arterial aneurysms. Nontraumatic HAAs are often asymptomatic and are typically discovered incidentally during imaging for unrelated conditions. However, they pose a significant risk of rupture, which can lead to life-threatening hemorrhaging. We present the case of a 65-year-old male with an asymptomatic saccular aneurysm of the proper hepatic artery diagnosed incidentally on CT scan. Further cross-sectional imaging confirmed the diagnosis and revealed no evidence of rupture. The patient underwent successful interventional endovascular repair using a covered stent under local anesthesia. This case emphasizes the use of minimally invasive techniques of interventional radiology in the management of complex vascular pathologies.